The importance of resilience and integration for the future European financial system - Karlheinz Walch; Benjamin Weigert (CESifo GmbH, 2024)
The idea of a Banking Union emerged in the aftermath of the global financial crisis. Ten years on, two of its three pillars, the Single Supervisory Mechanism and the Single Resolution Mechanism, have proven to be a success with regard to financial integration and stability. In this Policy Brief, experts from the Deutsche Bundesbank explain why, in times of structural change, it is crucial to complete the Banking Union and advance the Capital Markets Union.
Keywords: 330